2019
DOI: 10.1080/17483107.2019.1664649
|View full text |Cite
|
Sign up to set email alerts
|

Assistive technology selection to outcome assessment: the benefit of having a service delivery protocol

Abstract: This article has been republished with minor changes. These changes do not impact the academic content of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
7
0
3
Order By: Relevance
“…Similar trends have also been observed in previous studies conducted in other countries, which have shown that general practitioners and case managers have limited knowledge about AT in general [12,30,44,45]. Previous studies have also shown different perspectives among users, professionals and suppliers when assessing the needs for assistive technology [22][23][24][25]. Moreover, another study conducted in Norway revealed a lack of knowledge about assistive activity technology among important actors in the field of assistive activity technology [19].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar trends have also been observed in previous studies conducted in other countries, which have shown that general practitioners and case managers have limited knowledge about AT in general [12,30,44,45]. Previous studies have also shown different perspectives among users, professionals and suppliers when assessing the needs for assistive technology [22][23][24][25]. Moreover, another study conducted in Norway revealed a lack of knowledge about assistive activity technology among important actors in the field of assistive activity technology [19].…”
Section: Discussionsupporting
confidence: 80%
“…However, to date, studies on the overall service delivery process for AT have been few [4]. Furthermore, identifying particular outcomes has shown to be challenging due to the differing mandates and interests of the varied stakeholders [22]. In the Matching Person and Technology assessment process [23], consumer perspectives are considered to be affected by psychological and sociocultural factors.…”
Section: Introductionmentioning
confidence: 99%
“…First, improving the efficacy of automatically delivered step instructions and thus improving the participants' performance of multistep activities can be considered a highly valued objective within any rehabilitation context (Desmond et al, 2018;Lancioni et al, 2017;Lin et al, 2018;O'Neill et al, 2018;Pérez-Fuster et al, 2019). The possibility of approaching such an objective with relatively simple and accessible technology makes the objective realistic for a number of daily contexts irrespective of the fact that their technical expertness and financial resources may be fairly limited (Boot et al, 2018;Borg, 2019;De Witte et al, 2018;Scherer, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The cost of the present technology system may be estimated at about US $600 (ie, approximately US $150 for the Samsung smartphone, US $200 for the 4 Philips Hue sensors, US $100 for the 4 mini speakers, and US $150 for the Philips Hue Bridge, the Philips Hue smart bulb, and the 4G Long-Term Evolution Wi-Fi router). Although this cost is significant, one may argue that the present technology system (1) can be one of the few options available to enable people with intellectual and visual disabilities to manage independent occupation and mobility and ( 2) is fairly easy to operate for personnel in charge of the sessions and friendly for the participants [41][42][43][44]. The main obstacle rehabilitation professionals may encounter in accessing such a technology system is represented by the fact that it is not a ready-made (off-the-shelf) tool but needs to be set up through the aforementioned commercial components.…”
Section: Principal Findingsmentioning
confidence: 99%